Formal education programmes for senior house officers: comparison of experience in three hospital specialties. Issue 912 (1st October 2001) - Flett, A; Baker, M; Williams, J
Abstract : This study was designed to compare the attendance rate of senior house officers (SHOs) in three specialties at formal educational events, examine experiences of protected time, use of educational objectives, and perceived barriers to attendance and evaluate differences found in the context of variations in training practice within each specialty. A quantitative questionnaire survey was completed by Trent region SHOs in obstetrics and gynaecology, general medicine, and accident and emergency posts. An independent researcher visited a selection of educational programme events over a two month span, recorded attendances, and administered the questionnaire. Attendance rates ranged from 40.8% of those in obstetrics and gynaecology jobs to 55.4% of those in accident and emergency jobs. The questionnaire findings found that service commitments were a major obstacle to attendance for the majority of those in obstetrics and gynaecology and general medicine jobs, while relatively few of the accident and emergency SHOs specified any barriers. SHOs in accident and emergency jobs had significantly more protected time for education and found educational objectives to be more widely used by senior staff. The findings suggest that the planned integration of formal education programmes with appropriate working pattern systems—in this case full shifts within accident and emergency departments—will result in SHOs receiving a better deal in terms of provision and structure of education.